Tax Revenue and Nigeria Economic Growth - Onoja Eneche, Emmanuel; Stephen, Ibrahim Ademu (European Journal of Economics and Business Studies, 2021)
This study examines the relationship between Tax Revenue and Nigeria Economic Growth. In order to achieve this objective, data was gathered through secondary means. Tax Revenue is proxy by Petroleum Profit Tax, Value Added Tax and Companies Income Tax, while Economic Growth is proxy by Gross Domestic Product. Data collected were analyzed with the aid of the Stata computer software. The study revealed that Petroleum Profit Tax (oil tax revenue) has a positive but no significant relationship with Nigeria Economic Growth, while Value Added Tax and Companies Income Tax (non-oil Tax Revenue) have significant relationship with Nigeria Economic Growth. The study recommends that government should minimize the wide spread corruption and leakages prevalent in tax administration in Nigeria, and transparently and judiciously account for tax revenue generated through the provision of more quality public goods and services, and need not to increase the rates of Value Added Tax and Companies Income Tax in the short run, but to closely monitor the operations of companies engaged in petroleum operations to minimize tax evasion, and as well as support the development of entrepreneurial activities in order to significantly increase Tax Revenue so as to sustain the significant relationship of VAT and CIT (non-oil tax) revenue with Nigeria Economic Growth.